2018
DOI: 10.1097/ccm.0000000000003351
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Nutrition Status Expressed as Body Mass Index z Score With Outcomes in Children With Severe Sepsis: A Secondary Analysis From the Sepsis Prevalence, Outcomes, and Therapies (SPROUT) Study*

Abstract: There is considerable variation in nutrition status for children with severe sepsis treated across this selected network of PICUs from different geographic regions. Severe undernutrition was independently associated with higher all-cause ICU mortality in children with severe sepsis. Severe overnutrition was independently associated with greater ICU length of stay in childhood survivors of severe sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…BMI has long been considered to be one of the strongest risk factors for serious and critical illness. As researches [ 30 32 ] shown, for intensive care unit patients receiving endotracheal intubation, higher BMI was correlated with higher mortality and longer length of stay. Liu et al [ 33 ] reported that severe patients with COVID-19 had higher BMI.…”
Section: Discussionmentioning
confidence: 99%
“…BMI has long been considered to be one of the strongest risk factors for serious and critical illness. As researches [ 30 32 ] shown, for intensive care unit patients receiving endotracheal intubation, higher BMI was correlated with higher mortality and longer length of stay. Liu et al [ 33 ] reported that severe patients with COVID-19 had higher BMI.…”
Section: Discussionmentioning
confidence: 99%
“…True validity of the AMC against a “gold standard,” such as SGA, has not yet been published and is clearly needed. Notwithstanding the need for further validation work, the use of the AMC and the PMI tools has been useful in measuring malnutrition in hospitalized adult and pediatric patients and linking that condition with important clinical outcomes, including mortality, hospital length of stay (adults), complications (pediatrics), and readmissions . .…”
Section: Discussionmentioning
confidence: 99%
“…In the pediatric population, similar results have been observed with 3 published studies to date evaluating malnutrition as identified by the PMI and outcomes (see Table 6). [46][47][48] Increased odds of 30-day complications following surgery in children with Crohn's disease was demonstrated in those identified as mildly, moderately, or severely malnourished using the z-score BMI single indicator. 46 This was observed only in mild (OR = 2.1 [P = 0.04]) and severely (OR 3.3 [P = 0.03]) malnourished patients.…”
Section: Malnutrition Characteristics and Outcomesmentioning
confidence: 99%
See 2 more Smart Citations